Primary care utilisation in different patients’ profiles with cardiovascular risk factors - Sara Malo; Lina Maldonado; María José Rabanaque; Irantzu Bengoa-Urrengoechea; Sara Castel-Feced; María Antonia Sánchez-Calavera; Isabel Aguilar-Palacio (BMC Health Services Research)
Abstract Background This study aimed to identify profiles of patients with cardiovascular disease (CVD) risk factors, based on their sociodemographic and clinical characteristics, and to analyse how their complexity is related to their frequency of visits in Primary Care. Methods Observational longitudinal study conducted in the Spanish CArdiovascular Risk factors for HEalth Services research (CARhES) cohort. Individuals older than 15 with hypertension, type 2 diabetes mellitus (DM) and/or dyslipidaemia in 2017 were selected and followed until 2021. Cluster analyses were performed to identify patients’ profiles according to age, sex and morbidity burden. Characteristics and annual visits in Primary Care in the different profiles were described. Panel data models were applied to study the variability of the frequency of visits to both physicians and nurses in Primary Care in the profiles across different time points. Results In this population-based cohort of 446,998 individuals, different profiles were identified among those with hypertension, type 2 DM and/or dyslipidaemia. Profiles comprising the elderly showed the highest morbidity burden. Among the profiles of individuals under 80, those that included women had a higher burden than profiles with men. This higher complexity was associated with higher frequency of Primary Care visits, regardless of the patient’s socioeconomic level and depopulation level of his/her Basic Health Area. Conclusions Women and the elderly comprised the profiles with the highest morbidity burden and Primary Care attendance. Tailoring care and resources according to the complexity profile is essential to ensure that patients receive the best possible care based on their needs.